Recognition and inhibition of SARS-CoV-2 by humoral innate immunity pattern recognition molecules - Stravalaci, Matteo; Pagani, Isabel; Paraboschi, Elvezia Maria; Pedotti, Mattia; Doni, Andrea; Scavello, Francesco; Mapelli, Sarah N; Sironi, Marina; Perucchini, Chiara; Varani, Luca; Matkovic, Milos; Cavalli, Andrea; et al. (Nature immunology, 2022)
The humoral arm of innate immunity includes diverse molecules with antibody-like functions, some of which serve as disease severity biomarkers in coronavirus disease 2019 (COVID-19). The present study was designed to conduct a systematic investigation of the interaction of human humoral fluid-phase pattern recognition molecules (PRMs) with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Of 12 PRMs tested, the long pentraxin 3 (PTX3) and mannose-binding lectin (MBL) bound the viral nucleocapsid and spike proteins, respectively. MBL bound trimeric spike protein, including that of variants of concern (VoC), in a glycan-dependent manner and inhibited SARS-CoV-2 in three in vitro models. Moreover, after binding to spike protein, MBL activated the lectin pathway of complement activation. Based on retention of glycosylation sites and modeling, MBL was predicted to recognize the Omicron VoC. Genetic polymorphisms at the MBL2 locus were associated with disease severity. These results suggest that selected humoral fluid-phase PRMs can play an important role in resistance to, and pathogenesis of, COVID-19, a finding with translational implications.